O17.3 Pre-exposure prophylaxis (PREP) eligibility and barriers to uptake among persons who inject drugs recruited from a syringe exchange program (SEP). (8th July 2017) - Roth, Alexis M; Aumaier, Brenna; Piecara, Brogan L; Szep, Zsofia; Chavis, Martha; Pol, Barbara Van Der
Abstract : Introduction: Despite demonstrated clinical efficacy, little research has focused on implementing pre-exposure prophylaxis (PrEP) programs to prevent HIV among persons who inject drugs (PWID). We sought to determine the proportion of PWID meeting PrEP eligibility criteria and their attitudes towards PrEP as a first step in this process. Methods: Participants were English-speaking PWID age ≥18 years recruited from a syringe exchange program in Northeastern United States. They self-obtained specimens for gonorrhoea and chlamydia screening and completed a survey assessing factors hypothesised to impact PrEP eligibility and uptake. Eligibility was calculated based on CDC clinical guidelines and included injection drug use plus any affirmative response to: sharing syringes, recent or current STI, sex exchange, having a sex partner of HIV positive or unknown status, inconsistent condom use with a high number of sex partners and opioid replacement therapy all within 6 months. Results: Of 138 participants, 47% were women, 80% white with median age of 31. Eligibility was high (90.3%). Compared to men, women were more likely to report engaging in: vaginal sex, sex with a person of HIV positive or unknown status; sex exchange, greater numbers of sex partners, and screen positive for STI. Willingness to take PrEP was high (88.9% vs 71.0% among women and men, p<0.02). However, potential barriers to uptake were common and included: embarrassment (45%), anxiety (51.6%), not wanting to disclose PrEP use to a romantic partner (51.4%), being uninsured (30.1%), and not accessing providers where PrEP is routinely offered (52.9%). Conclusion: Despite being recruited from a SEP, 9:10 participants were eligible for PrEP. While participants found PrEP acceptable, they reported multiple barriers to uptake including lack of access to clinical care and insurance. To optimise and scale PrEP programs for this population additional research is needed. However, data suggest uptake will remain sub-optimal unless tailored interventions are developed.